Reliability, Validity, and Factor Structure of Teachers’ Success Evaluation Questionnaire - Elhami , Hamidreza; Mirhashemi , Malek; Pasha Sharifi, Hasan (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to design and test the structural model of the effects of life experiences, personality traits and thinking styles on the success of teachers with the mediation of job interests. Methodology: In order to achieve this goal, 234 teachers were selected using a cluster sampling method among high school teachers in Bojnourd city as the sample of this study. At first, their success rate was assessed by managers and students through a researcher-made questionnaire. Then Sternberg-Wagner Stress Thinking Styles Questionnaire, Five Factor Questionnaire, Short Form Personality Traits, Job Awareness Questionnaire and Researcher-made Life-Exercise Questionnaire were completed by the teachers. At first, the descriptive characteristics of the data from the research sample were examined. In the next step, based on the path analysis method, the research model was extracted based on the relationships between the variables and finally, the fit of the extracted model with the experimental data was evaluated using the structural equation modeling method. Findings: The results indicated that the personality traits of psychosis, extroversion and direct consistency, and personality trait of conscientiousness indirectly through external job interests, have a significant effect on the prediction of teachers' professional success. Also, Kurds of thinking styles, cognitive thinking, forms of thinking styles, group thinking, levels of thinking styles, holistic thinking, and the domains of thinking styles, external thinking, and the forms of thinking, thinking, and marital styles are also Both indirectly and indirectly through interpersonal and interpersonal interests, and the work of thinking styles, peer-to-peer, indirectly through external job interests, coefficients have a significant effect on the prediction of the professional success of teachers. Conclusion: successful teachers include content knowledge, teaching skills, classroom management, communication skills and motivation, creativity development, interaction power.